Sign Languages in Audiovisual Media: Towards a Taxonomy from a Translational Point of View - Tamayo, Ana (Journal of Audiovisual Translation, 2022)
Sign language (SL), sign language interpreting (SLI) and sign language translation (SLT) have often been overlooked in both theoretical and more practical approaches within Audiovisual Translation (AVT) studies. This is a theoretical contribution that aims at presenting a taxonomy for the classification of SL, SLI and SLT that might serve to encourage and develop descriptive accounts in the field. This objective is achieved through a review of previous literature on sign language, media accessibility and descriptive AVT studies. To this end, a brief introduction to how SLT and SLI are conducted in the area of audiovisual (AV) content will be presented. A short discussion from an AVT perspective on source languages (L1s), target languages (L2s) and third languages (L3s) will follow, including observations on the role of SLs in AV production, the stages at which SLs are implemented, and the possible translation modes for these languages. Reflections here will lead to the proposal of the first ever taxonomy for the analysis of those AVT modes which include the presence of SLs in AV content. Finally, conclusions will focus on the importance of fostering methodologically strong descriptive studies on SL translation and interpreting from an AVT perspective. Lay summary Audiovisual Translation Studies and Sign Language Studies have been ever-growing research fields since the 1060’s and 70’s, but Audiovisual Translation Studies have systematically ignored Sign language, sign language interpreting and sign language translation. This article is hopes to contribute with a solid theoretical and methodological approach to Audiovisual Translation Studies to include the study of sign language in audiovisual content. Firstly, a review on previous literature on the related fields of study is conducted. Secondly, an introduction on how sign language translation and interpreting can be seen in TV and in other media is presented. Thirdly, a discussion from the Audiovisual Translation point of view on languages involved in audiovisual production is offered. All this leads to a classification for the analysis of sign language in the media that might serve to encourage descriptive studies. Finally, conclusions focus on the importance of more studies on how sign languages and their translation and interpreting is carried out in the media.